The oldest Apterodontinae (Hyaenodontidae, “Creodonta”) from the middle Eocene of Dor el Talha (Libya) - (:unkn) unknown (My University, 2010)
After the Fayum record of Egypt, the late middle Eocene Dor El Talha escarpment (Central Libya) has provided one of the richest Paleogene fauna of North Africa. Currently, six orders of placental mammals, including primates, have been found in this outcrop. Here, we present the results of the first study of hyaenodontid (“Creodonta”) remains: dental and postcranial specimens discovered in 2007 and 2009 (Franco-Libyan cooperative program between University of Poitiers and University of El Fateh in Tripoli) and the historical material collected by Savage in 1965 and stored at the NHM (London). The oldest members of Apterodontinae are identified. Apterodontines were hitherto recorded in the late Eocene and Oligocene of Europe (France, Germany) and Africa (Egypt, Kenya). The best preserved Libyan material is a subcomplete mandible and maxillar with several associated postcranial elements. It is morphologically close to the late Eocene Apterodon macrognathus, recovered in the lower part of the Jebel Qatrani Formation (Fayum). Its teeth resemble those of the Egyptian species notably in its tubercular morphology and the bearing of a M2 metacone and a prominent parastyle of M3 on its maxillar. Postcranial elements, in particular the distal humerus, the proximal ulna and the tarsal bones indicate an ability to supinate, which excludes a cursorial locomotor type. In a first approach, the bulbous morphology of the teeth perhaps reflects an omnivorous or durophagous diet. Phylogenetic relationships of the Apterodontinae within the Hyaenodontidae have been poorly discussed. However, we note that dental features as the lack of the metaconid and the presence of a talonid on lower molars can make it close to some African and Eurasian hyainailourines.
Keywords: African Research